Pharmaceutical and personal care products in domestic wastewater and their removal in anaerobic treatment systems: Septic tank – up flow anaerobic filter. (2016)
In several countries around the world, Pharmaceutical and Personal Care Products (PPCPs) exist in aquatic environments, a fact that increases the awareness within the scientific community with respect to their possible fate and environment effects. This research presents a preliminary monitoring of use, consumption and presence of PPCPs in wastewater from a treatment plant in a rural area of Pereira (Colombia). Domestic sewage is treated in a septic tank followed by an Up-Flow Anaerobic Filter and its effluent is discharged into the Otún River, upstream of the water intake of the supply system of the city. The compounds monitored in this research included ibuprofen, naproxen, diclofenac, aspirin, ketoprofen, caffeine, galaxolide, tonalide and dihydrojasmonate. An adapted method of multi-residue analysis was used, which is based on solid phase extraction with hydrophilic-lipophilic balance cartridges, and determination by gas chromatography-mass spectrometry. The removal efficiencies demonstrated that the treatment plant could eliminate less than 50% of dihydrojasmonate, diclofenac and galaxolide existing in wastewater; concentration of aspirin, naproxen and tonalide could only be reduced in 15%; and caffeine, ibuprofen and ketoprofen were not removed. Results provided basic information to decide over the necessity of complementary treatments for effluents from systems with the mentioned units.